2020
DOI: 10.1039/c9cp05984a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of the Janus MoSSe/WSSe superlattice nanoribbon: a first-principles study

Abstract: The electronic structure properties of Janus MoSSe/WSSe superlattice nanoribbons (SLNRs) are investigated by first-principles calculations. The ribbon width, combination ratio and period length have a great effect on the properties of the SLNRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…[ 58–65 ] In our previous contribution, the bandgap of Janus MoSSe is calculated with PBE‐GGA and HSE06 and the value of the obtained bandgap is 1.58 and 2.09 eV. [ 66 ] Obviously, the former functional agrees with the experimental value of 1.68 eV. Therefore, all the calculations in this work are carried out using PBE functional.…”
Section: Theoretical Methods and Modelingmentioning
confidence: 68%
“…[ 58–65 ] In our previous contribution, the bandgap of Janus MoSSe is calculated with PBE‐GGA and HSE06 and the value of the obtained bandgap is 1.58 and 2.09 eV. [ 66 ] Obviously, the former functional agrees with the experimental value of 1.68 eV. Therefore, all the calculations in this work are carried out using PBE functional.…”
Section: Theoretical Methods and Modelingmentioning
confidence: 68%
“…34 In particular, the band structure of the Janus MoSSe/WSSe superlattice can be changed from type-I to type-II by intrinsic structural parameters and used as a photocatalyst for water splitting, 35 which can also be effectively tuned by external strain and electric field. 36 The Janus MoSSe/ WSSe superlattice nanoribbon can even be transformed as half-metal and magnetic material using decent ribbon width, 37 while the influence of superlattice configuration on the mechanical behaviors of the 2D in-plane heterostructure is rarely reported. In addition, the intrinsic bending at the interface of in-plane Janus MoSSe/WSSe heterostructure decides the mechanical strength, which can provide a theoretical guidance for further devices.…”
Section: Kai Renmentioning
confidence: 99%
“…Transition metal dichalcogenides (TMDs) have been widely studied due to their unique spintronic, magnetic, optical, and electronic structural properties, 21–25 proving their great potentials for applications. However, the out-of-plane mirror symmetry of the TMD molecules may restrict the freedom of electrons, affecting the spintronic device-related applications, 26–29 Yu et al used Se atoms in MoS 2 to replace the S atoms in one of the layers to successfully prepare Janus MoSSe, and investigated MoSSe/WSSe superlattice nano, which experimentally successfully modulated the electronic structure as well as the magnetic properties of MoSSe/WSSe superlattice nano, 30 which also showed that MoSSe and other Janus materials have potential in the field of spintronics.…”
Section: Introductionmentioning
confidence: 99%